Efficient Desulfurization of 4-Methyldibenzothiophene Using H5PV2Mo10O40/TiO2: A Catalytic Approach - Anggraini, Ana; Jefri, Jefri; Komis; Lesbani, Aldes (Indonesian Journal of Material Research, 2025)
Oxidation desulfurization (ODS) is an effective method to remove sulfur compounds from fuels by converting them into more polar oxidized forms that are easier to extract. In this study, H₅PV₂Mo₁₀O₄₀/TiO₂ catalysts were synthesized and characterized using FT-IR spectroscopy. The FT-IR spectra confirmed the successful impregnation of polyoxometalate into the TiO₂ matrix, indicated by the appearance of Ti-O and O-Ti-O vibrations, while the typical H₅PV₂Mo₁₀O₄₀ peaks remained detectable. The performance of the H₅PV₂Mo₁₀O₄₀/TiO₂ catalyst in the desulfurization of 4-methyldibenzothiophene (4-MDBT) was studied based on variations in reaction time, catalyst mass, temperature, and amount of H₂O₂. The optimal conditions obtained were a reaction time of 2 hours, a catalyst mass of 0.05 g, a temperature of 60°C, and a volume of H₂O₂ of 5 mL, with a maximum sulfur conversion of 99.0%. These results indicate that H₅PV₂Mo₁₀O₄₀/TiO₂ has potential as an efficient ODS catalyst.